2001
DOI: 10.1017/s1464793100005625
|View full text |Cite
|
Sign up to set email alerts
|

Sources and bioavailability of phosphorus fractions in freshwaters: a British perspective

Abstract: This paper seeks a perspective on the forms of phosphorus which promote aquatic eutrophication, with the particular quest of establishing their sources. A short background traces the development of understanding of nutrient enrichment and the suppositions about the relative contributions of agriculture, sewage and detergent residues. Most aquatic systems, and their primary producers, are naturally deficient in biologically-available phosphorus. Aquatic plants have evolved very efficient phosphorus uptake mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(110 citation statements)
references
References 95 publications
0
104
0
6
Order By: Relevance
“…No fi toplâncton, Ankistrodesmus pertence à associação de espécies características de condições eutrófi cas e hipereutrófi cas (Reynolds 1984). Trabalhos sobre fi toplâncton relataram, ainda, a ocorrência frequente de Dictyosphaerium pulchellum em sistema eutrófi co (Rosen 1981) e seu usual aumento populacional com a eutrofi zação (Margalef 1983).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…No fi toplâncton, Ankistrodesmus pertence à associação de espécies características de condições eutrófi cas e hipereutrófi cas (Reynolds 1984). Trabalhos sobre fi toplâncton relataram, ainda, a ocorrência frequente de Dictyosphaerium pulchellum em sistema eutrófi co (Rosen 1981) e seu usual aumento populacional com a eutrofi zação (Margalef 1983).…”
Section: Discussionunclassified
“…É frequentemente reportado como nutriente limitante do crescimento algal em diferentes regiões climáticas do globo (Hecky & Kilham 1988, Reynolds & Davies 2001, podendo atuar de forma indireta sobre vários processos, como sobre o fl uxo e dinâmica do nitrogênio em ecossistemas oligotrófi cos (Dodds & Priscu 1990) e até mesmo levando à limitação por outros nutrientes, como a sílica (Schelske & Stoermer 1971).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For practical purposes, the bioavailable P is often 54 measured by colorimetric methods and reported as soluble reactive phosphorus (SRP) or 55 dissolved reactive phosphorus (DRP), an approach followed in water quality monitoring 56 programmes worldwide. However, it has been shown that SRP often overestimates the 57 bioavailable P fraction (Boström et al, 1988;Reynolds and Davies, 2001;Rigler, 1968). 58…”
Section: Moorleghem Et Al 2011) 48mentioning
confidence: 99%
“…A carga maior na sub-bacia 12, separada do conjunto formado pelas sub-bacias contíguas ao exutório, deve-se à existência de maior área agrícola contínua. Segundo Reynolds & Davies (2001), as lavouras aumentam drasticamente as perdas de nutrientes em relação às áreas florestadas. Na figura 4, observa-se a distribuição mensal da exportação total de P simulada no exutório da bacia.…”
Section: Adição De Fósforo Ao Solo Como Fertilizanteunclassified